MARKETING COMMUNICATION STRATEGIES IN THE PROMOTION OF TERRITORIAL COMMUNITIES - Lyndiuk , А. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
The article describes the essence, meaning and impact of marketing communications on the promotion of territorial communities. It was determined that the marketing communications of communities are aimed at forming and conveying their clear and attractive image to the target audience to achieve certain strategic goals. Distinctive features of marketing communications of territorial communities relative to commercial structures are formulated, which include a wider range of target audiences, complexity of tasks, as well as the need for cooperation with various interested parties. The main factors that influence the marketing communications of local self-government bodies and determine the specifics of the approaches and tools used in communication strategies are considered. Recommendations for the formation and implementation of effective marketing communication strategies for territorial communities have been developed, the main elements of which are the analysis of the target audience, the development of clear goals, the analysis of the competitive environment, the use of modern digital technologies, the creation of a unique brand, the integration of various communication channels, the involvement of the community, regular measurement of effectiveness, adaptation to changes and ensuring sustainable development. Marketing communications are important for increasing the recognition of territories, attracting investments, stimulating tourism and strengthening their positive reputation. They can help communities achieve competitive advantages at the national and international levels, thanks to the improvement or generation of new methods, approaches and principles of operational activities based on the use of modern knowledge. An effective communication strategy results in the achievement of community goals, including economic, social and environmental directions. Successful application of the proposed recommendations will contribute to increasing the competitiveness of territorial communities, ensuring their sustainable development and improving the quality of the residents’ lives.